A clinical case of Merkel cell carcinoma - R. V. Saranyuk; T. A. Gosteva; E. D. Tsnobiladze (Сибирский научный медицинский журнал, 2023)
Merkel cell carcinoma is a rare, rapidly progressive, aggressive skin tumor with frequent metastasis and high mortality. The disease is a multifactorial pathology resulting from the interaction of endogenous and exogenous risk factors. Timely detection of Merkel cell carcinoma is important in the management and prognosis of the patient, because the disease is often associated with other neoplastic processes not only in the skin but also in other organs. This article presents a clinical case of Merkel cell carcinoma and deals with the issues of its etiopathogenesis, differential diagnostics and therapy.